2020
DOI: 10.1108/et-11-2018-0236
|View full text |Cite
|
Sign up to set email alerts
|

Student internship experiences: learning about the workplace

Abstract: PurposeThe purpose of this study was to explore the experiences of engineering student interns, as well as the perceptions of internship supervisors.Design/methodology/approachThe study was designed to investigate internships as a complex social phenomenon in the field, through the use of an inductive qualitative design grounded in a naturalistic paradigm guided by theories of learning and socialisation. The researchers used semistructured interviews of 24 engineering student interns and 10 internship supervis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…During their internships, graduates will get feedback on their skills and competencies, either formally or on a day-to-day basis. Also, they will learn about adequate qualifications and necessary skills in a desired field of work (Zehr and Korte, 2020). Finally, their perspective of being able to address challenges at work in the future due to personal attributes and abilities, will change by successfully accomplishing work assignments during their internship, which are all supposed to foster graduates' perception of the social and human capital they possess, their confidence in their skills and, hence, their belief in being employable (Bandura, 1977; Rothwell et al , 2008).…”
Section: Graduates' Career-entry Worries: the Contribution Of High-quality Internshipsmentioning
confidence: 99%
“…During their internships, graduates will get feedback on their skills and competencies, either formally or on a day-to-day basis. Also, they will learn about adequate qualifications and necessary skills in a desired field of work (Zehr and Korte, 2020). Finally, their perspective of being able to address challenges at work in the future due to personal attributes and abilities, will change by successfully accomplishing work assignments during their internship, which are all supposed to foster graduates' perception of the social and human capital they possess, their confidence in their skills and, hence, their belief in being employable (Bandura, 1977; Rothwell et al , 2008).…”
Section: Graduates' Career-entry Worries: the Contribution Of High-quality Internshipsmentioning
confidence: 99%
“…Additionally, company supervisors receive small preparation prior to supervising interns. So they do not know how much work students can handle during an internship (Zehr and Korte, 2020). Moreover, internship goals for companies and educational institutions usually do not align.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zehr found that students did not look for connections between the classroom and the workplace, making it difficult to apply skills from one setting to the other. Therefore, it can be concluded that the success of the internship program is influenced by supervisors at work, work environment, job descriptions, and supervisors on campus [8].…”
Section: Introductionmentioning
confidence: 99%